Global Climate Crisis: Challenge and Opportunity for Indonesia - Pattinussa, Jhon Maxwell Josua; Aaron, Pablo (AEGIS : Journal of International Relations, 2025)
AbstractThis manuscript explores Indonesia's complex position in the global climate crisis, with the central argument that Indonesia’s success in climate leadership hinges on bridging persistent tensions between economic priorities and environmental justice. Indonesia faces mounting pressure to balance economic growth with climate commitments. . Following the US withdrawal from the Paris Agreement and the introduction of NDC 3.0, Indonesia faces immense pressure to balance economic growth with climate commitments. Despite its substantial forest carbon sinks and ambitious net-zero targets, Indonesia's reliance on coal and weak enforcement of environmental policies hinder progress. The country’s carbon market (IDXCarbon) and natural resource endowment,especially nickel for EV batteriesposition it as a potential green economy leader. However, challenges persist, including low carbon credit prices, fragmented ASEAN markets, and elite-driven economic policies prioritizing coal exports over environmental stewardship. This paper argues that Indonesia can leverage regional cooperation under ASEAN’s carbon frameworks, align carbon markets with international standards, and negotiate debt-for-nature swaps to strengthen its green transition. Ultimately, while international forums highlight Indonesia's proactive climate diplomacy, domestic realities reveal persistent tensions between economic priorities and environmental considerations.. Indonesia's success or failure in managing this paradox will have far-reaching consequences for its people and the global climate system. The authors conclude that Indonesia must pursue a holistic, inclusive approach integrating political will, equitable financing, and rigorous governance to actualize its green industrial ambitions and establish itself as a leading actor in the Global South's climate transformation.Keywords: Indonesia, Climate Crisis, Green Economy, Carbon Market, Environmental Justice.